Developing Center of Excellence Vocational High Schools: Analysis of the Influence of Agile Leadership and School Organizational Culture - Widiawati Widiawati; Fifin Wildanah; Singgih Ginanjar (STAI Hubbulwathan Duri, 2025)
Being designated as a Center of Excellence Vocational School (CEVHS) is a prestigious achievement, indicating that the institution has passed a rigorous, credible selection process. Several state vocational schools in Bukittinggi City have earned this designation, prompting significant institutional transformation to improve learning quality and promote the Pancasila Student Profile. This study employed a descriptive correlational design to examine the influence of agile leadership and school organizational culture on CEVHS development. The population included 228 teachers from SMK N 1 and SMK N 2 Bukittinggi. A stratified proportional random sampling method was used, based on education level and years of service, resulting in a sample size determined using the Slovin formula. Data were collected via a Likert-scale questionnaire and analyzed using mean scores, percentages, and the Respondent Achievement Level (TCR). Multiple linear regression analysis was conducted using SPSS software. The results revealed a significant positive influence of agile leadership and school organizational culture on the development of CEVHS, with a combined contribution of 53%. These findings highlight the crucial role of leadership and organizational culture in supporting the transformation of vocational schools into Centers of Excellence. Effective implementation of these factors can enhance learning quality and align educational outcomes with national educational goals.